The driven factors on new electronic commerce adoption by Small and Medium Enterprise (SME) in Klang Valley / Nur Atiqah Zainuddin...[et.al] - Zainuddin, Nur Atiqah; Ismail, Maymunah; Ahmad, Nurul Zamratul Asyikin; Shariff, Sharina; Mazalan, Maz Izuan; Ab Kadir, Mohd Sufian (Academy of Contemporary Islamic Studies, 2018)
In transforming into digitalization economy, the electronic commerce or e-commerce had embarked to the new business methods. It is the most important tool in business market especially in digital online marketing. It’s create more competitive in marketing strategies among the business player around the world and this study focusing on Small Medium Enterprise formerly SME. Currently, SME industry players was recorded in increasing trends and the largest business participation to the country’s performance including Malaysia. E-commerce is among the best and easy tool by SME with the role to expand their business, and meet the invisible customer across how far the customer’s location, time and place. It is very convenient also to customers do shopping through online. The intention of this study are to determine the driven factors on e-commerce adoption by SME in Klang Valley and to identify the most influential factor on e-commerce adoption. A conceptual framework comprises of five factors that are relative advantage, compatibility, complexity, top management support and knowledge and resources constraint is being taken from variables for research. Multiple regression analysis generated is being carried out to test hypothesis and to establish the causal effect of relative advantage, compatibility, complexity, top management support and knowledge and resources constraint towards adoption of e-commerce. The result shows that relative advantage, compatibility, and top management support and knowledge have significant and positive impact on adoption of e-commerce. Therefore, this study concluded that the relative advantage, compatibility, top management support and knowledge has significant strong relationship with adoption of e-commerce. Meanwhile, complexity and resources constraint are found not statistically significant in affecting the adoption of e-commerce. Compatibility factor is found to be the most significant factor in affecting e-commerce adoption of SMEs. Therefore, the government should take initiatives and pay more attention to promote e-commerce among SME because SME has potential market growth and high contribution for economic development in Malaysia.